Propaganda Methods in Foreign Films on Television: An Analytical Study of Channels (MBC2 and FOX MOVIES) - Abed, Omar Younus; Hameed, Shareef Saeed (ALBAHITH ALALAMI, 2024)
Foreign films are one of the most important media tools used by advertisers to promote a specific idea or goal through the propaganda methods employed in foreign films aired on television. The researcher employed a content analysis method to achieve the research objective. The research sample consisted of 30 American-produced films, which topped the global list of best films, known as the Box Office list. The researcher reached several conclusions, including: The use of pathos or emotional appeal is the most prevalent, followed by the emergence of display or transient advertising methods in film content, and then gradually followed by other methods according to their classification. It was noted that the total number of appearances of the combined propaganda methods was 1834 repetitions, which is a clear indication that American foreign films use propaganda methods to convey advertising messages that serve the goals of advertisers.